CoDesign for Discovery in Social Sciences and Humanities : Addressing the heterogeneous needs of a community in digital scholarship - De Paoli, Stefano; Forbes, Paula; Andreini, Giulio; Maryl, Maciej; Błaszczyńska, Marta (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2024)
GoTriple is a novel discovery platform for Social Sciences and Humanities (SSH) in Europe. Discovery is a phase of research where scholars seek to locate resources for their work, such as publications or previous projects. The paper details the work done for involving the SSH community in the codesign of GoTriple, focusing on the research discovery activities. It is an investigation of the user needs and barriers toward digital discovery for the SSH community, conducted through codesign. This work encompassed interviews, a questionnaire, codesign workshops and evaluation activities. The paper reports on some outcomes for the codesign and how user needs were identified and served by novel designs supporting discovery for SSH. This process of design is both concerned with creating digital tools for discovery and with the creation of a community of users that could make the platform thrive. The main contribution of the work is therefore the identification of the user needs for digital discovery in SSH and a series of insights on the design with the user community. The paper comprises a report on how codesign principles do support such work.